Pengaruh Content Marketing dan Brand Awareness terhadap Minat Beli pada Produk Glad 2 Glow - Nurlaeli Azizah; Siti Sarah; Ridho Riadi Akbar (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
Glad 2 Glow has entered the attention space of Indonesian skincare consumers through short video content, accessible pricing, and a light brand personality that is familiar to young social media users. This study examines how content marketing and brand awareness are associated with consumers' purchase interest in Glad 2 Glow products. A quantitative survey was conducted with 96 respondents who had encountered Glad 2 Glow content on social media. The data were assessed using item validity, reliability, descriptive statistics, classical assumption checks, multiple linear regression, and hypothesis testing. The findings show that content marketing encourages purchase interest by clarifying product benefits, reducing uncertainty, and helping consumers compare skincare alternatives before buying. Brand awareness also strengthens purchase interest because a recognizable name, visual identity, and repeated exposure make the brand easier to recall in a crowded skincare category. Simultaneously, both variables account for 39.6% of the variation in purchase interest. The study indicates that Glad 2 Glow needs to balance viral content with credible product education, consistent visual identity, and communication that converts audience attention into purchase consideration